2004
DOI: 10.1111/j.0022-202x.2004.23322.x
|View full text |Cite
|
Sign up to set email alerts
|

Sunburn Cell Formation, Dendritic Cell Migration, and Immunomodulatory Factor Production After Solar-Simulated Irradiation of Sunscreen-Treated Human Skin Explants In Vitro

Abstract: Using human skin explants, we investigated the effects of two different sunscreen preparations containing a chemical UVB filter alone [sun protection factor (SPF) 5.2] or UVA+UVB filter [SPF 6.2] on sunburn cell formation, dendritic cell (DC) migration, CD86- and CD1a-positive cell number, and tumor necrosis factor alpha (TNFalpha) and interleukin (IL)-1, IL-10, and IL-12 production in the skin after irradiation with different doses of solar-simulated UV radiation. Sunscreen- or placebo-treated skin explants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Sunscreens are applied 15-20 min before irradiation, a time interval which is sufficient to exert their effect [7,[25][26][27] . As there was no suppression of skin erythema when the Physiogel AI was applied 20 min before UV irradiation we suggest that these substances have no direct sunblocker effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sunscreens are applied 15-20 min before irradiation, a time interval which is sufficient to exert their effect [7,[25][26][27] . As there was no suppression of skin erythema when the Physiogel AI was applied 20 min before UV irradiation we suggest that these substances have no direct sunblocker effects.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The role of UVA (wavelengths 320-400 nm) in these processes and the protection afforded by sunscreens are still debated. [3][4][5][6] Indeed, some studies showed that UVA radiation was immunosuppressive, [7][8][9][10][11][12] whereas others suggested that it had no effects on immune functions 3,[13][14][15] or was immunoprotective. 3,16,17 Potential explanation for these conflicting results mainly lies in the source and doses of UVA as well as the protocols used to evaluate the cutaneous immune effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet (UV) radiation‐mediated immunosuppression is thought to be one of the most important factors for the development of skin cancer 1,2 . The role of UVA (wavelengths 320–400 nm) in these processes and the protection afforded by sunscreens are still debated 3–6 . Indeed, some studies showed that UVA radiation was immunosuppressive, 7–12 whereas others suggested that it had no effects on immune functions 3,13–15 or was immunoprotective 3,16,17 .…”
mentioning
confidence: 99%
“…However, a small number of studies provide the opposite evidence. For example, a comparison in human skin explants of the protection provided by two sunscreens matched for sun protection factor but with differing UVA transmission found that neither the number of SSUV‐induced apoptotic sunburn cells, the expression of the cytokines IL‐1, IL‐10, IL‐12 or TNF‐α nor the migration of epidermal dendritic cells differed (17). Furthermore, Liardet et al .…”
Section: Discussionmentioning
confidence: 99%